2003
DOI: 10.1159/000071465
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Touch Stimulation Acutely Alters Corticosterone Levels and Glucocorticoid Receptor Gene Expression in the Neonatal Rat

Abstract: Environmental manipulation early in life can alter the development of the hypothalamic-pituitary-adrenal (HPA) axis by mechanisms that are still unclear. The aim of the present work was to study the acute effects of postnatal touch stimulation, in an attempt to understand the mechanism by which touch stimulation early in life alters the HPA response to stress in adult animals. Rat pups were gently brushed for 15 min daily during the 1st postnatal week. Serum corticosterone levels were determined by radioimmuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 33 publications
4
53
0
3
Order By: Relevance
“…Moreover, artificial tactile stimulation derived from simply stroking the pups with a brush is sufficient to increase NGFI-A association with the exon 1 7 promoter. These findings are consistent with an earlier report showing that the same 'stroking' of pups increases hippocampal GR expression [38] and dampens HPA responses to stress [39]. These findings suggest that it is the tactile stimulation associated with pup LG that is critical for the effect on hippocampal NGFI-A association with the exon 1 7 GR promoter.…”
Section: How Do Parental Signals Alter Dna Methylation?supporting
confidence: 92%
“…Moreover, artificial tactile stimulation derived from simply stroking the pups with a brush is sufficient to increase NGFI-A association with the exon 1 7 promoter. These findings are consistent with an earlier report showing that the same 'stroking' of pups increases hippocampal GR expression [38] and dampens HPA responses to stress [39]. These findings suggest that it is the tactile stimulation associated with pup LG that is critical for the effect on hippocampal NGFI-A association with the exon 1 7 GR promoter.…”
Section: How Do Parental Signals Alter Dna Methylation?supporting
confidence: 92%
“…Jutapakdeegul et al (2003) report that enhanced tactile stimulation (pup stroking with a brush) over the first week of life results in increased hippocampal GR expression in adulthood. Previous studies suggest that such effects as well as those on NGFI-A expression are mediated by increased hippocampal 5-HT activity at 5-HT 7 receptors that are positively coupled to cAMP (Mitchell et al, 1990(Mitchell et al, , 1992Meaney et al, 2000).…”
mentioning
confidence: 96%
“…The Reverse transcriptase polymerase chain reaction (RT-PCR) was carried out using the Qiagen one step RT-PCR kit. PCR amplifications of SAT1 employed primers 5 -ACAGGC-GACATTCTCATCCT-3 (forward) and 5 -GTTTCA-GTGGCCTTCACCAT-3 (reverse), giving rise to a 426 base pair amplicon 24 , and β-actin (housekeeping gene) primers 5 -CCCAGAGCAAGAGAGGCATC-3 (forward) and 5 -CTCAGGAGGAGCAATGATCT-3 (reverse), giving rise to a 830 base pair amplicon 25 . Primers were obtained from the Bioservice Unit of the National Science and Technology Development Agency, Thailand.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group demonstrated that treatment of mixed cell cultures with 10 µM Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) for 12 h and 24 h reduces SAT1 protein level as demonstrated by immunocytochemical and quantitative immunoreactivity analysis 20 . We now report the effects of Aβ(25-35) on SAT1 expression in rat cortical primary cell cultures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation